Confocal Laser Endomicroscopy Can Improve the Diagnosis Rate and Range Assessment of Patients With Conflicting Chronic Atrophic Gastritis Results of White Light Endoscopic and Pathological Diagnosis - Pang, Suya; Yao, Hailing; Jiang, Chen; Zhang, Qin; Lin, Rong (Frontiers in Oncology, 2022)
Background and aims: Chronic atrophic gastritis (CAG) are closely related to the development of gastric cancer. However, the diagnostic accuracy of white light endoscopy (WLE) biopsy for CAG is poor. The diagnostic role and efficacy of confocal laser microscopy (CLE) in CAG missed under WLE biopsy remains unclear. Methods: This study is a single-center prospective study that included 21 patients from 1349 patients who underwent WLE and biopsy and whose WLE results were CAG, but pathological results were not. Then all these patients received CLE examination and underwent targeted biopsies and five-point standard biopsies. The sensitivity, specificity, and accuracy of CLE diagnosis and targeted biopsy were analyzed. Results: The pathological results of five-point standard biopsies in 21 patients were CAG, and 17 patients (81.0%) were intestinal metaplasia (IM). According to the image diagnosis of CLE, there were 19 cases (90.5%) CAG and 14 cases (66.7%) IM of these 21 patients. According to the targeted biopsy of CLE, 17 cases (81.0%) of CAG were diagnosed, and 14 cases (66.7%) of IM. There was no significant difference between CLE image diagnosis and five-point standard biopsies in terms of atrophy severity score (p=0.927), IM severity score (p=0.250), atrophy scope score (p=0.781) and IM scope score (p=0.195). For CAG, the sensitivity and accuracy of CLE image diagnosis were higher than those of CLE targeted biopsies (90.5% vs. 81.0%, p=0.331), but for IM, the diagnosis was the same. Conclusions: CLE can improve the diagnosis rate of CAG, and can increase the comprehensive assessment of the scope and severity of CAG.